DEVELOPMENT OF NEW CONTROL ALGORITHMS FOR A ROBOTIC ARM EQUIPPED WITH A 3D SCANNING OR MACHINE VISION SYSTEM - Кадыролдина, Альбина (Вестник ВКТУ им. Д. Серикбаева, 2022)
Manipulator robots perform many complex actions and solve important tasks in the industry (welding, cutting, spaying, sorting, etc.). This article discusses the geometric problems of the kinematics of the robot, in order to ensure the smoothness of movement without instantaneous stops at the corners of the trajectory. The problem of equipping the robot with additional 3D scanning or machine vision system to control such situations is considered. It is proposed to use a method for recognizing the dominant points of the trajectory, in particular, corner points, based on image processing with specialized masks.